Exploring Hadith Hasan: A Fresh Perspective al-Jami' al-Sahih al-Sunan al-Tirmidzi - Anam, Wahidul; Sulaeman, Mubaidi (Diroyah : Jurnal Studi Ilmu Hadis, 2023)
This study aims to evaluate the quality of the traditions classified as á¸¥asan in Sunan Al-Tirmidzi's Al-Jami' Al-á¹¢aá¸¥Ä«h, a topic that has attracted considerable attention among á¸¥adÄ«th scholars. Using a literature review methodology combined with a qualitative approach, this study has not only discovered a new qualification for assessing the quality of traditions in AbÅ« Isa Al-Tirmidzi's Al-Jamiâ€™ Al-á¹¢aá¸¥Ä«h, referred to as á¸¥asan á¹£aá¸¥Ä«h traditions but also expanded its scope beyond the existing findings. This research has revealed that the emergence of the á¸¥asan á¸¥adÄ«th has prompted strong scholarly engagement, signalling the ever-evolving nature of á¸¥adÄ«th studies. This evolution requires researchers to always be ready to re-evaluate classical texts, encourages continuous exploration of new perspectives and promotes acceptance of the potential for new classifications to emerge within the field. Furthermore, this study has illustrated Al-Tirmidzi's pioneering efforts to reshape the categorisation of á¸¥adÄ«th. More than simply introducing the á¹£aá¸¥Ä«h á¸¥adÄ«th, Al-Tirmidzi cleverly combined this classification with other existing categories, including the á¹£aá¸¥Ä«h gharib á¸¥adÄ«th and the á¹£aá¸¥Ä«h gharib á¸¥adÄ«th thus enriching the intricacies of á¸¥adÄ«th classification methodology. The implications of this innovative approach go beyond Al-Tirmidzi's work and affect the broader landscape of á¸¥adÄ«th scholarship. Moreover, the findings of this study have substantial legal ramifications in Islamic jurisprudence. The revelation that certain traditions classified as á¸¥asan have the status of á¹£aá¸¥Ä«h implies that these texts can serve as a valid legal basis despite their initially inferior category. This discovery underscores the dynamic interaction between á¸¥adÄ«th scholarship and Islamic jurisprudence, where á¸¥adÄ«th classification has a real impact on the legal framework of faith. In sum, this study underscores the dynamic and ever-evolving nature of the field of á¸¥adÄ«th studies as well as the important role played by scholars such as Al-Tirmidzi in reshaping the classification. It emphasises the need for constant exploration of classical texts and readiness to adapt to evolving perspectives to ensure that the field remains at the forefront of Islamic scholarship and jurisprudence.Â